Chemical treatment method for improving surface smoothness of laser 3D printing titanium alloy

Through multi-stage chemical treatment method, surface treatment solutions with different viscosity and components, combined with immersion and ultrasonic stirring technology, the problem of high surface roughness of laser 3D printing titanium alloy components is solved, and the effective reduction of surface roughness and the adaptability of complex structures is achieved.

CN119588958AActive Publication Date: 2025-03-11AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411789749.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Laser 3D printing titanium alloy components have high surface roughness, and existing methods are difficult to effectively reduce, especially in complex structures such as blind holes.

Method used

The multi-stage chemical treatment method is adopted to prepare surface treatment solutions with different viscosity and components, and use immersion and ultrasonic stirring technology to gradually reduce the roughness of the surface of the titanium alloy.

Benefits of technology

Under a relatively small amount of thinning, the surface roughness of the titanium alloy is significantly reduced, which is suitable for complex structures and avoids the problem of excessive thinning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588958A_ABST
    Figure CN119588958A_ABST
Patent Text Reader

Abstract

The invention relates to a chemical treatment method for improving the surface smoothness of a laser 3D printing titanium alloy, and belongs to the technical field of titanium alloy surface treatment. The chemical treatment method comprises the following steps: preparing a plurality of surface treatment solutions including a first surface treatment solution, a second surface treatment solution and a third surface treatment solution; the titanium alloy workpiece is placed in a first surface treatment solution to be subjected to first-stage soaking treatment till the surface roughness of the titanium alloy workpiece is reduced to 15-18 microns; the titanium alloy workpiece is placed in a second surface treatment solution to be subjected to second-stage soaking treatment till the surface roughness of the titanium alloy workpiece is reduced to 8-10 microns; the titanium alloy workpiece is placed in a third surface treatment solution to be subjected to third-stage soaking treatment till the surface roughness of the titanium alloy workpiece is reduced to be smaller than 5 micrometers; wherein the viscosities of the first surface treatment solution, the second surface treatment solution and the third surface treatment solution are sequentially reduced, and the adsorption quantity of the surfactant is sequentially increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of titanium alloy surface treatment, and in particular to a chemical treatment method for improving the surface finish of laser 3D printed titanium alloy. Background Art

[0002] Laser 3D printing technology is an advanced additive manufacturing technology with the characteristics of high precision, speed and efficiency. It is widely used in aerospace, automobile manufacturing, medical, construction and other fields. Using laser 3D printing technology for integrated structural design can produce lightweight and high-strength parts and components.

[0003] Titanium alloys are widely used in aerospace, marine, automotive and other fields due to their high specific strength and excellent corrosion resistance. However, the surface roughness of titanium alloy components printed by laser 3D is generally high, usually around R30-40μm or even higher. If the conventional chemical milling process is used to reduce the surface roughness to less than a few microns, a thinning amount of several millimeters is generally required, which is impossible to reserve in advance for laser 3D printed parts. And because titanium alloys are difficult-to-process materials, there are problems such as high friction coefficient, high grinding temperature and severe grinding wheel bonding when using grinding. Moreover, even if high-quality surface grinding is achieved by certain means, it is difficult to implement operations when dealing with complex structures such as blind holes printed by laser 3D. Summary of the invention

[0004] In view of the above analysis, an embodiment of the present invention aims to provide a chemical treatment method for improving the surface finish of laser 3D printed titanium alloy, so as to solve the problem that the existing method is difficult to polish the surface of laser 3D printed titanium alloy with high roughness.

[0005] An embodiment of the present invention provides a chemical treatment method for improving the surface finish of a laser 3D printed titanium alloy, comprising:

[0006] Step S1, preparing a plurality of surface treatment solutions, wherein the plurality of surface treatment solutions include a first surface treatment solution, a second surface treatment solution and a third surface treatment solution; the plurality of surface treatment solutions all include a passivating agent, a dissolving agent, a viscosity regulating agent, a surfactant and a solvent; the passivating agent is nitric acid, and the dissolving agent is hydrofluoric acid;

[0007] Step S2, placing the titanium alloy workpiece in a first surface treatment solution for a first stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 15-18 μm;

[0008] Step S3, placing the titanium alloy workpiece in a second surface treatment solution for a second stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 8-10 μm;

[0009] Step S4, placing the titanium alloy workpiece in a third surface treatment solution for a third stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to less than 5 μm;

[0010] Among them, the viscosities of the first surface treatment solution, the second surface treatment solution and the third surface treatment solution decrease in sequence, and the adsorption amounts of the surfactants on the titanium alloy surface increase in sequence.

[0011] Further, in the first surface treatment solution, the viscosity regulator includes ethylene glycol and disodium hydrogen phosphate, and the surfactant is polyethylene glycol;

[0012] In the second surface treatment solution, the viscosity regulator includes ethylene glycol and disodium hydrogen phosphate, and the surfactant includes polyethylene glycol and polyoxyethylene laurate;

[0013] In the third surface treatment solution, the viscosity regulator is ethylene glycol, and the surfactant includes polyethylene glycol and dodecylphenol polyoxyethylene ether;

[0014] Preferably, the second surface treatment solution and the third surface treatment solution further include hexamethylenetetramine.

[0015] Furthermore, in the first surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2-1:2.5, the concentration of ethylene glycol is 100-150 mL / L, the concentration of disodium hydrogen phosphate is 20-25 g / L, the concentration of polyethylene glycol is 1-2 g / L, and the molecular weight is ≥6000.

[0016] Further, in the second surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1.5-1:2, the concentration of ethylene glycol is 80-100 mL / L, the concentration of disodium hydrogen phosphate is 15-20 g / L, the concentration of polyethylene glycol is 0.5-1 g / L, and the molecular weight is 1000≤≤2000, the concentration of polyoxyethylene laurate is 0.2-0.4 g / L, and the concentration of hexamethylenetetramine is 0.1-0.3 g / L.

[0017] Further, in the third surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1-1:1.5, the concentration of disodium hydrogen phosphate is 10-15 g / L, the concentration of ethylene glycol is 20-50 mL / L, the concentration of polyethylene glycol is 0.2-0.5 g / L and the molecular weight is 200≤≤400, the concentration of dodecylphenol polyoxyethylene ether is 0.1-0.2 g / L, and the concentration of hexamethylenetetramine is 0.1-0.3 g / L.

[0018] Furthermore, in step S3 and step S4, ultrasonic stirring is performed while the immersion treatment is performed, and the ultrasonic power is 800-2000W.

[0019] Further, in step S2, when the surface roughness of the titanium alloy workpiece reaches the range of 15 to 18 μm, the thinning amount of the titanium alloy workpiece is controlled to be within 150 μm.

[0020] Further, in step S3, when the surface roughness of the titanium alloy workpiece reaches the range of 8 to 10 μm, the total thinning amount of the titanium alloy workpiece is controlled to be within 200 μm.

[0021] Further, in step S4, when the surface roughness of the titanium alloy workpiece reaches 5 μm or less, the total thinning amount of the titanium alloy workpiece is controlled to be within 300 μm.

[0022] Furthermore, during the three-stage immersion treatment, if the total thinning amount of the titanium alloy workpiece reaches the maximum thinning amount requirement of the current stage, and the surface roughness still does not reach the target requirement of the current stage, the ultrasonic power of the ultrasonic stirring is adjusted, and / or the concentration of at least one of the passivator, viscosity regulator and surfactant in the surface treatment solution is adjusted.

[0023] Furthermore, the concentration of at least one of the passivating agent, the viscosity regulating agent and the surfactant is increased by 15 to 20%.

[0024] Furthermore, in step S2, if the surface roughness has not been reduced to below 18 μm when the thinning amount of the titanium alloy workpiece reaches 150 μm, the concentration of at least one of nitric acid, ethylene glycol and polyethylene glycol in the first surface treatment solution is increased by 15-20% and the immersion treatment is performed again.

[0025] Further, in step S3, when the surface roughness of the titanium alloy workpiece reaches the range of 8 to 10 μm, the total thinning amount of the titanium alloy workpiece is controlled within 200 μm;

[0026] If the surface roughness has not been reduced to less than 10 μm when the thinning amount of the titanium alloy workpiece reaches 200 μm, the ultrasonic power is reduced and the immersion is continued;

[0027] If the surface roughness is still not reduced to below 10 μm when the ultrasonic power is reduced to 0, the concentration of at least one of nitric acid, ethylene glycol, polyethylene glycol and polyoxyethylene laurate in the second surface treatment solution is increased by 15-20% and the immersion treatment is repeated.

[0028] Further, in step S4, when the surface roughness of the titanium alloy workpiece reaches less than 5 μm, the total thinning amount of the titanium alloy workpiece is controlled within 300 μm;

[0029] If the surface roughness of the titanium alloy workpiece has not been reduced to less than 5 μm when the thinning amount reaches 300 μm, the ultrasonic power is reduced and the immersion is continued;

[0030] If the surface roughness is still not reduced to below 5 μm when the ultrasonic power is reduced to 0, the concentration of at least one of nitric acid, ethylene glycol, polyethylene glycol and dodecylphenol polyoxyethylene ether in the third surface treatment solution is increased by 15-20% and the immersion treatment is repeated.

[0031] Compared with the prior art, the chemical treatment method of the present invention can achieve at least one of the following beneficial effects:

[0032] 1. The present invention reduces the surface roughness of laser 3D printed titanium alloy workpieces in three stages by preparing surface treatment solutions with different viscosities, the amount of surfactant adsorbed on the titanium alloy surface, and dissolution / passivation properties. The surface roughness can be reduced to the maximum extent with a relatively small thinning amount, and is more suitable for titanium alloy workpieces with high roughness of more than 30 μm obtained by laser 3D printing, a near-net-shape forming technology.

[0033] 2. The present invention adopts a chemical treatment method, which can reduce the surface roughness only by immersion and ultrasonic stirring. Compared with the mechanical polishing method, it is more adaptable to complex surface structures, especially inner hole or blind hole structures.

[0034] 3. In the three-stage immersion treatment, when the total thinning amount of the titanium alloy workpiece reaches the maximum thinning amount requirement of the current stage, but the surface roughness still does not reach the target requirement of the current stage, the present invention can avoid excessive thinning by adjusting the process parameters of the immersion treatment (for example, ultrasonic power and the concentration of some components in the surface treatment solution) and continue immersing, thereby achieving a reduction in surface roughness while ensuring that the thinning amount meets the requirements.

[0035] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0037] Figure 1 This is a surface morphology diagram of the titanium alloy workpiece of Example 1 of the present invention before chemical surface treatment.

[0038] Figure 2 This is a surface morphology diagram of the titanium alloy workpiece after chemical surface treatment according to Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0040] An embodiment of the present invention provides a chemical treatment method for improving the surface finish of laser 3D printed titanium alloy, the method comprising:

[0041] Step S1, preparing a plurality of surface treatment solutions, the plurality of surface treatment solutions comprising a first surface treatment solution, a second surface treatment solution and a third surface treatment solution, the plurality of surface treatment solutions comprising a passivating agent, a dissolving agent, a viscosity regulating agent, a surfactant and a solvent; the passivating agent is nitric acid, and the dissolving agent is hydrofluoric acid;

[0042] Step S2, placing the titanium alloy workpiece in a first surface treatment solution for a first stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 15-18 μm;

[0043] Step S3, placing the titanium alloy workpiece in a second surface treatment solution for a second stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 8-10 μm;

[0044] Step S4, placing the titanium alloy workpiece in a third surface treatment solution for a third stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to less than 5 μm;

[0045] Among them, the viscosities of the first surface treatment solution, the second surface treatment solution and the third surface treatment solution decrease in sequence, and the adsorption amount of the surfactant on the surface of the titanium alloy increases in sequence.

[0046] The present invention reduces the surface roughness of a laser 3D printed titanium alloy workpiece in three stages by preparing surface treatment solutions with different viscosities, the amount of surfactant adsorbed on the titanium alloy surface, and dissolution / passivation properties, thereby achieving the maximum reduction in surface roughness with a relatively small thinning amount.

[0047] Specifically, the present invention soaks titanium alloys of different roughness in surface treatment solutions of different viscosities, so that titanium alloys of different roughness are adapted to surface treatment solutions of different viscosities; since the higher the dissolving viscosity, the stronger the surface leveling ability, when the surface roughness of the titanium alloy is larger, the viscosity of the surface treatment solution used is relatively high.

[0048] At the same time, titanium alloys with different roughness must also be adapted to surface treatment solutions with different adsorption amounts on the titanium alloy surface, so that the surfactant can be fully adsorbed in the depressions, thereby achieving the effect of reducing the dissolution rate at the depressions and gradually smoothing the surface.

[0049] Furthermore, the present invention adopts a chemical treatment method, which can reduce the surface roughness only by immersion, and is more adaptable to complex surface structures, especially inner hole or blind hole structures, compared with the mechanical polishing method.

[0050] In some embodiments, in the first surface treatment solution, the viscosity regulator includes ethylene glycol and disodium hydrogen phosphate, and the surfactant is polyethylene glycol. That is, the first surface treatment solution includes nitric acid (passivating agent), hydrofluoric acid (dissolving agent), ethylene glycol (viscosity regulator), disodium hydrogen phosphate (viscosity regulator) and polyethylene glycol (surfactant).

[0051] In the second surface treatment solution, the viscosity control agent includes ethylene glycol and disodium hydrogen phosphate, and the surfactant includes polyethylene glycol and polyoxyethylene laurate ether. That is, the second surface treatment solution includes nitric acid (passivating agent), hydrofluoric acid (dissolving agent), ethylene glycol (viscosity control agent), disodium hydrogen phosphate (viscosity control agent), polyethylene glycol (surfactant) and polyoxyethylene laurate ether (surfactant).

[0052] In the third surface treatment solution, the viscosity regulator is ethylene glycol, and the surfactant includes polyethylene glycol and dodecylphenol polyoxyethylene ether. That is, the third surface treatment solution includes nitric acid (passivating agent), hydrofluoric acid (dissolving agent), ethylene glycol (viscosity regulator), polyethylene glycol (surfactant) and dodecylphenol polyoxyethylene ether (surfactant).

[0053] In the present invention, titanium alloys with different roughness are adapted to surfactants of different types and molecular sizes, so that the surfactants can be fully adsorbed in the depressions on the surfaces of titanium alloys with different roughness, so as to achieve the effect of reducing the dissolution rate at the depressions and gradually smoothing the surface.

[0054] In some embodiments, the second surface treatment solution and the third surface treatment solution further include hexamethylenetetramine. In the embodiments of the present invention, hexamethylenetetramine is used as a complexing agent, which effectively dissolves the surface of the titanium alloy by forming a stable complex with metal ions, and can effectively prevent the redeposition of dissolved metal ions, thereby maintaining the smoothness of the titanium alloy surface.

[0055] In some embodiments, the solvent of each surface treatment solution is preferably deionized water.

[0056] In some embodiments, in the first surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2-1:2.5, the concentration of ethylene glycol is 100-150 mL / L, the concentration of disodium hydrogen phosphate is 20-25 g / L, the concentration of polyethylene glycol is 1-2 g / L, and the molecular weight is ≥6000.

[0057] For example, the concentration of nitric acid can be 150mL / L, 155mL / L, 160mL / L, 165mL / L, 170mL / L, 175mL / L, 180mL / L, 185mL / L, 190mL / L, 195mL / L, 200mL / L. The concentration ratio of hydrofluoric acid to nitric acid can be 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5. The concentration of ethylene glycol can be 100mL / L, 110mL / L, 120mL / L, 130mL / L, 140mL / L, 150mL / L. The concentration of disodium hydrogen phosphate can be 20g / L, 21g / L, 22g / L, 23g / L, 24g / L, 25g / L. The concentration of polyethylene glycol is 1g / L, 1.1g / L, 1.2g / L, 1.3g / L, 1.4g / L, 1.5g / L, 1.6g / L, 1.7g / L, 1.8g / L, 1.9g / L, 2g / L, and the molecular weight can be 6000, 7000, 8000, 9000, 10000, etc.

[0058] In the second surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1.5-1:2, the concentration of ethylene glycol is 80-100 mL / L, the concentration of disodium hydrogen phosphate is 15-20 g / L, the concentration of polyethylene glycol is 0.5-1 g / L, and the molecular weight is 1000≤≤2000, the concentration of polyoxyethylene laurate ether is 0.2-0.4 g / L, and the concentration of hexamethylenetetramine is 0.1-0.3 g / L.

[0059] For example, the concentration of nitric acid can be 150mL / L, 155mL / L, 160mL / L, 165mL / L, 170mL / L, 175mL / L, 180mL / L, 185mL / L, 190mL / L, 195mL / L, 200mL / L. The concentration ratio of hydrofluoric acid to nitric acid can be 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2. The concentration of ethylene glycol can be 80mL / L, 85mL / L, 90mL / L, 95mL / L, 100mL / L. The concentration of disodium hydrogen phosphate can be 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L. The concentration of polyethylene glycol is 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L, and the molecular weight can be 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000. The concentration of lauric acid polyoxyethylene ether can be 0.2 g / L, 0.25 g / L, 0.3 g / L, 0.35 g / L, 0.4 g / L, and the concentration of hexamethylenetetramine can be 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.25 g / L, 0.3 g / L.

[0060] In the third surface treatment solution, the concentration of nitric acid is 150-200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1-1:1.5, the concentration of disodium hydrogen phosphate is 10-15 g / L, the concentration of ethylene glycol is 20-50 mL / L, the concentration of polyethylene glycol is 0.2-0.5 g / L and the molecular weight is 200≤≤400, the concentration of dodecylphenol polyoxyethylene ether is 0.1-0.2 g / L, and the concentration of hexamethylenetetramine is 0.1-0.3 g / L.

[0061] For example, the concentration of nitric acid can be 150mL / L, 155mL / L, 160mL / L, 165mL / L, 170mL / L, 175mL / L, 180mL / L, 185mL / L, 190mL / L, 195mL / L, 200mL / L. The concentration ratio of hydrofluoric acid to nitric acid can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5. The concentration of ethylene glycol can be 20mL / L, 25mL / L, 30mL / L, 35mL / L, 40mL / L, 45mL / L, 50mL / L. The concentration of disodium hydrogen phosphate can be 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L. The concentration of polyethylene glycol is 0.2g / L, 0.25g / L, 0.3g / L, 0.35g / L, 0.4g / L, 0.45g / L, 0.5g / L, and the molecular weight can be 200, 250, 300, 350, 400. The concentration of dodecylphenol polyoxyethylene ether can be 0.1g / L, 0.11g / L, 0.12g / L, 0.13g / L, 0.14g / L, 0.15g / L, 0.16g / L, 0.17g / L, 0.18g / L, 0.19g / L, 0.2g / L, and the concentration of hexamethylenetetramine can be 0.1g / L, 0.15g / L, 0.2g / L, 0.25g / L, 0.3g / L.

[0062] The present invention adjusts the concentrations of the solvent, the passivator, the viscosity regulator, the surfactant and the complexing agent in each surface treatment solution so that each surface treatment solution is suitable for treating titanium alloy surfaces at different stages with different roughnesses, so that the viscosity of the solution, the adsorption amount of the surfactant, the ratio of surface passivation and the solution reach an optimal balance, so that the titanium alloy surfaces with different roughnesses are gradually flattened during the dissolution process, and the difficulty of dissolving the titanium alloy surface is avoided.

[0063] Among them, the increase in the concentration of the passivating agent (i.e., nitric acid) will slow down the dissolution of the titanium alloy surface, making the surface flat, but its concentration is too high will cause slow dissolution. The increase in the concentration of the viscosity control agent can increase the viscosity, and the increase in the concentration of the surfactant can increase the adsorption amount of the surfactant on the surface, so that the surface is gradually flattened during the dissolution process; however, too high a concentration of the viscosity control agent or the surfactant will make the dissolution difficult. Therefore, the present invention controls each component within a suitable range, which can ensure that the titanium alloy surface can be gradually dissolved and flattened, and avoids the slow dissolution resulting in low processing efficiency or difficulty in dissolving, which causes the titanium alloy surface to be unable to be flattened.

[0064] In some embodiments, ultrasonic stirring is performed during the immersion treatment in step S3 and step S4. The present invention can rapidly diffuse the dissolved substances on the surface of the titanium alloy by ultrasonic stirring the surface treatment solution, promote uniform dissolution of the titanium alloy surface, and thus gradually smoothen the surface of the titanium alloy.

[0065] In some embodiments, the ultrasonic power is 800 to 2000 W, for example, 800 W, 900 W, 1000 W, 1200 W, 1400 W, 1500 W, 1600 W, 1800 W, 2000 W. Lower ultrasonic power will slow down the transmission of surface substances and strengthen the adsorption of substances, thereby increasing the viscosity of the surface liquid layer, which is conducive to surface flattening; but when the ultrasonic power is too low or ultrasonic stirring is not performed, the solute may accumulate too much, the viscosity may be too high or the adsorption may be too strong, causing dissolution difficulties. Therefore, the present invention not only helps to flatten the surface of the titanium alloy by controlling the ultrasonic power, but also avoids the dissolution difficulties caused by the dosage of the surface solutes.

[0066] In some embodiments, in steps S2 to S4, the temperature of each surface treatment solution is controlled at 25 to 30°C, for example, 25±2°C, 26±2°C, 27±2°C, 28±2°C, 29±2°C, 30±2°C, etc., and then the immersion treatment is performed. Among them, ±2°C refers to the allowable temperature fluctuation range during the immersion process.

[0067] In addition, in steps S3 and S4, the solution temperature of the surface treatment solution may be slightly higher than the solution temperature of the first surface treatment solution in step S2, so that the surface treatment solution has a lower viscosity and is suitable for titanium alloys with reduced surface roughness.

[0068] In some embodiments, in step S2, when the surface roughness of the titanium alloy workpiece reaches the range of 15 to 18 μm, for example, reaches 15 μm, 16 μm, 17 μm, 18 μm, etc., the thinning amount of the titanium alloy workpiece is controlled within 150 μm, that is, the maximum thinning amount is controlled to be 150 μm.

[0069] In some embodiments, in step S3, when the surface roughness of the titanium alloy workpiece reaches the range of 8 to 10 μm, for example, when the surface roughness reaches 8 μm, 9 μm, 10 μm, etc., the total thinning amount of the titanium alloy workpiece is controlled within 200 μm, that is, the maximum thinning amount is controlled to be 200 μm.

[0070] In some embodiments, in step S4, when the surface roughness of the titanium alloy workpiece reaches below 5 μm, the total thinning amount of the titanium alloy workpiece is controlled to be within 300 μm, that is, the maximum thinning amount is controlled to be 300 μm.

[0071] Compared with conventional titanium alloy chemical milling technology, the present invention controls the thinning amount of the titanium alloy after immersion in various surface treatment solutions. It avoids excessive thinning that is not conducive to maintaining the shape structure of the titanium alloy workpiece in 3D printing, and is more suitable for improving the surface finish of near-net-shape titanium alloy workpieces such as 3D printing technology.

[0072] In some embodiments, in order to control the thinning amount of the titanium alloy workpiece, after the titanium alloy workpiece is immersed in each surface treatment solution, it is necessary to take out the titanium alloy workpiece at regular intervals to measure the surface roughness and total thinning amount of the titanium alloy workpiece.

[0073] Specifically, in steps S2, S3 and S4, after the titanium alloy workpiece is immersed in each surface treatment solution for 3 to 5 minutes, the titanium alloy workpiece is taken out to measure the surface roughness and the total thinning amount to determine whether the surface roughness meets the target requirements of the current treatment stage and whether the total thinning amount is within a predetermined range. If the measured surface roughness does not meet the target requirements, continue to immerse, and take out the workpiece for measurement every 1 to 1.5 minutes to avoid excessive treatment that causes the thinning amount of the titanium alloy to exceed the predetermined range, and also avoid frequent removal of the workpiece for measurement to affect the treatment efficiency.

[0074] In some embodiments, during the three-stage immersion treatment, if the total thinning amount of the titanium alloy workpiece reaches the maximum thinning amount requirement of the current stage, but the surface roughness still does not reach the target requirement of the current stage, it is necessary to adjust the process parameters of the immersion treatment and continue immersing to control the thinning amount and avoid excessive thinning.

[0075] Wherein, adjusting the process parameters of the immersion treatment includes adjusting the ultrasonic power of the ultrasonic stirring, and / or adjusting the concentration of at least one of the passivating agent, the viscosity regulating agent and the surfactant in the surface treatment solution.

[0076] Specifically, the ultrasonic power can be reduced; and / or the concentration of at least one of the passivating agent, the viscosity modifier and the surfactant can be increased by 15-20%. For example, the concentration of each of the above components can be increased by 15%, 16%, 17%, 18%, 19%, 20%, etc.

[0077] In some embodiments, in step S2, if the surface roughness has not been reduced to below 18 μm when the thinning amount of the titanium alloy workpiece reaches 150 μm, the concentration of at least one of nitric acid, ethylene glycol and polyethylene glycol in the first surface treatment solution is increased by 15-20% and the immersion treatment is performed again.

[0078] In step S3, if the surface roughness of the titanium alloy workpiece has not been reduced to less than 10 μm when the thinning amount reaches 200 μm, the ultrasonic power is reduced and the immersion is continued. If the surface roughness has not been reduced to less than 10 μm when the ultrasonic power is reduced to 0, the concentration of at least one of nitric acid, ethylene glycol, polyethylene glycol and lauric acid polyoxyethylene ether in the second surface treatment solution is increased by 15-20%, and the immersion treatment is repeated.

[0079] In step S4, if the surface roughness of the titanium alloy workpiece has not been reduced to less than 5 μm when the thinning amount reaches 300 μm, the ultrasonic power is reduced and the immersion is continued. If the surface roughness has not been reduced to less than 5 μm when the ultrasonic power is reduced to 0, the concentration of at least one of nitric acid, ethylene glycol, polyethylene glycol and dodecylphenol polyoxyethylene ether in the third surface treatment solution is increased by 15-20%, and the immersion treatment is repeated.

[0080] In the surface treatment solution, nitric acid is used as a passivating agent. The increase of its concentration will slow down the dissolution and make the surface smooth. Increasing its concentration by 15-20% can slow down the dissolution rate, avoid the surface from thinning too quickly, and avoid slow dissolution caused by too high a concentration. By appropriately increasing the concentration of ethylene glycol, the viscosity can be increased. By appropriately increasing the concentration of surfactants such as polyethylene glycol, the adsorption of surfactants on the surface can be increased. This can make the titanium alloy surface gradually smooth during the dissolution process, and also avoid the difficulty of dissolution caused by too high a concentration of both.

[0081] In steps S3 and S4, the transmission of the material on the titanium alloy surface can be slowed down by reducing the ultrasonic power, and the adsorption of the material can be strengthened, thereby increasing the viscosity of the surface liquid layer, which helps to flatten the surface and slow down the thinning of the titanium alloy. In addition, in steps S3 and S4, you can first try to adjust the ultrasonic power of the ultrasonic stirring. If adjusting the ultrasonic power can control the thinning amount while reducing the surface roughness, the cumbersome operation of adjusting the component concentration of the surface treatment solution is avoided, and the operation is simpler.

[0082] The following examples are used to further illustrate the chemical treatment method for improving the surface finish of laser 3D printed titanium alloy of the present invention.

[0083] Example 1

[0084] In this embodiment, a laser 3D printed Ti6Al4V bearing is subjected to chemical surface treatment, and its original surface roughness is about 37.6 μm (average value of three points). Figure 1 As shown, the surface is relatively rough. It is required to reduce the surface roughness to 5μm or less under the condition of not more than 300μm thinning. The specific steps of chemical surface treatment are as follows.

[0085] 1. Prepare three surface treatment solutions:

[0086] (1) preparing a first surface treatment solution with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid and disodium hydrogen phosphate; wherein the concentration of ethylene glycol is 150 mL / L, the concentration of polyethylene glycol is 2 g / L, and the molecular weight is 8000, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2.5, and the concentration of disodium hydrogen phosphate is 25 g / L;

[0087] (2) preparing a second surface treatment solution with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid, disodium hydrogen phosphate, polyoxyethylene laurate ether and hexamethylenetetramine; wherein the concentration of ethylene glycol is 100 mL / L, the concentration of polyethylene glycol is 1 g / L, and the molecular weight is 2000, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2, the concentration of disodium hydrogen phosphate is 20 g / L, the concentration of polyoxyethylene laurate ether is 0.4 g / L, and the concentration of hexamethylenetetramine is 0.2 g / L;

[0088] (3) A third surface treatment solution is prepared with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid, dodecylphenol polyoxyethylene ether and hexamethylenetetramine; wherein the concentration of ethylene glycol is 50 mL / L, the concentration of polyethylene glycol is 0.5 g / L, and the molecular weight is 400, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1.5, the concentration of disodium hydrogen phosphate is 15 g / L, the concentration of dodecylphenol polyoxyethylene ether is 0.2 g / L, and the concentration of hexamethylenetetramine is 0.2 g / L.

[0089] 2. Control the temperature of the first surface treatment solution within the range of 28±2℃, immerse the titanium alloy workpiece in the solution without stirring the solution. Take it out after 5 minutes and measure its surface roughness of about 23.2μm and the thinning amount of about 80μm. Continue to immerse the sample in the solution and take it out for measurement every 1 minute. When the total immersion time reaches 7 minutes, the surface roughness of the workpiece is measured to be about 17.3μm and the thinning amount is about 120μm.

[0090] 3. Control the temperature of the second surface treatment solution within the range of 30±2℃, immerse the titanium alloy workpiece in the solution, and place the container containing the solution in an ultrasonic cleaning machine with an ultrasonic stirring power of 1500W. After 3 minutes, take it out and measure its surface roughness of about 12.1μm, and the total thinning amount is about 180μm. Continue to immerse the sample in the solution, and take it out for measurement every 1 minute. When the total immersion time reaches 13 minutes, the surface roughness is measured to be about 7.5μm, and the thinning amount is about 230μm.

[0091] 4. Control the temperature of the third surface treatment solution within the range of 30±2℃, immerse the titanium alloy workpiece in the solution, and place the container containing the solution in an ultrasonic cleaning machine with an ultrasonic stirring power of 1500W. After 3 minutes, the surface roughness was measured to be about 5.2μm, and the total thinning amount was about 280μm. At this time, the thinning amount has approached the upper limit. The workpiece was immersed for another minute, and the surface roughness was measured to be about 4.5 microns, and the total thinning amount was about 300 microns. Figure 2 As shown, the surface of titanium alloy is smooth and clean.

[0092] Example 2

[0093] In this embodiment, a laser 3D printed TC11 titanium alloy compressor blade is subjected to chemical surface treatment, the original surface roughness of which is about 42.6 μm (three-point average), and it is required to reduce the surface roughness to 5 μm or less under the condition of a thinning amount not exceeding 300 μm. The specific steps of the chemical surface treatment are as follows.

[0094] 1. Prepare three surface treatment solutions:

[0095] (1) preparing a first surface treatment solution with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid and disodium hydrogen phosphate; wherein the concentration of ethylene glycol is 150 mL / L, the concentration of polyethylene glycol is 2 g / L, and the molecular weight is 8000, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2.5, and the concentration of disodium hydrogen phosphate is 25 g / L;

[0096] (2) preparing a second surface treatment solution with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid, disodium hydrogen phosphate, polyoxyethylene laurate ether and hexamethylenetetramine; wherein the concentration of ethylene glycol is 100 mL / L, the concentration of polyethylene glycol is 1 g / L, and the molecular weight is 2000, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:2, the concentration of disodium hydrogen phosphate is 20 g / L, the concentration of polyoxyethylene laurate ether is 0.4 g / L, and the concentration of hexamethylenetetramine is 0.3 g / L;

[0097] (3) A third surface treatment solution is prepared with deionized water, ethylene glycol, polyethylene glycol, nitric acid, hydrofluoric acid, dodecylphenol polyoxyethylene ether and hexamethylenetetramine; wherein the concentration of ethylene glycol is 50 mL / L, the concentration of polyethylene glycol is 0.5 g / L, and the molecular weight is 400, the concentration of nitric acid is 200 mL / L, the concentration ratio of hydrofluoric acid to nitric acid is 1:1.5, the concentration of disodium hydrogen phosphate is 15 g / L, the concentration of dodecylphenol polyoxyethylene ether is 0.2 g / L, and the concentration of hexamethylenetetramine is 0.3 g / L.

[0098] 2. Control the temperature of the first surface treatment solution within the range of 28±2°C, and immerse the titanium alloy workpiece in the solution without stirring the solution. Take it out after 5 minutes and measure its surface roughness to be about 27.1μm, and the thinning amount is about 90μm. Continue to immerse the sample in the solution, and take it out for measurement every 1 minute. When the total immersion time reaches 7 minutes, the surface roughness of the workpiece is measured to be about 21.5μm, and the thinning amount is about 140μm; when the total immersion time is 8 minutes, the surface roughness is measured to be about 19.0μm, and the thinning amount is about 160μm, which has exceeded the upper limit of 150μm, but the surface roughness has not reached the range of 15-18μm;

[0099] 3. Adjust the ethylene glycol concentration in the first surface treatment solution to 180 mL / L and the polyethylene glycol concentration to 2.3 g / L, and take a new workpiece and repeat step 2. After 5 minutes, the surface roughness was measured to be about 25.5 μm, and the thinning amount was about 80 μm. When the total immersion time reached 8 minutes, the surface roughness was measured to be about 17.8 μm, and the thinning amount was about 130 μm.

[0100] 4. Control the temperature of the second surface treatment solution within the range of 30±2℃, immerse the titanium alloy workpiece in the solution, and place the container containing the solution in an ultrasonic cleaning machine with an ultrasonic stirring power of 1500W. After 3 minutes, take it out and measure its surface roughness of about 14.1μm, and the total thinning amount is about 170μm. Continue to immerse the sample in the solution, and take it out for measurement every 1 minute. When the total immersion time reaches 15 minutes, the surface roughness is measured to be about 8.6μm, and the thinning amount is about 200μm.

[0101] 5. Control the temperature of the third surface treatment solution within the range of 30±2℃, immerse the titanium alloy workpiece in the solution, and place the container containing the solution in an ultrasonic cleaning machine with an ultrasonic stirring power of 1500W. After 3 minutes, the surface roughness was measured to be about 6.1μm, and the total thinning amount was about 300μm. At this time, the thinning amount has reached the upper limit, so the immersion treatment can no longer be continued, and the process needs to be adjusted again.

[0102] 6. Take a new sample and repeat steps 1 to 4. Turn off the ultrasonic stirring in step 5. After 3 minutes, the surface roughness measured by orientation is about 5.8μm, and the total thinning is about 280μm. Thereafter, measure once every 1 minute. When the total immersion time reaches 19 minutes, the surface roughness is about 5.3 microns and the total thinning is about 290μm. When the total immersion time reaches 20 minutes, the surface roughness is about 5.0 microns and the total thinning is about 300μm, which meets the process requirements.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A chemical treatment method for improving the surface finish of laser 3D printed titanium alloy, characterized in that: include: Step S1, preparing a plurality of surface treatment solutions, wherein the plurality of surface treatment solutions include a first surface treatment solution, a second surface treatment solution and a third surface treatment solution; The plurality of surface treatment solutions all include a passivator, a dissolving agent, a viscosity regulator, a surfactant and a solvent; the passivator is nitric acid, and the dissolving agent is hydrofluoric acid; Step S2, placing the titanium alloy workpiece in a first surface treatment solution for a first stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 15-18 μm; Step S3, placing the titanium alloy workpiece in a second surface treatment solution for a second stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to 8-10 μm; Step S4, placing the titanium alloy workpiece in a third surface treatment solution for a third stage of immersion treatment until the surface roughness of the titanium alloy workpiece is reduced to less than 5 μm; Among them, the viscosities of the first surface treatment solution, the second surface treatment solution and the third surface treatment solution decrease in sequence, and the adsorption amounts of the surfactants on the titanium alloy surface increase in sequence.

2. The method according to claim 1, characterized in that In the first surface treatment solution, the viscosity regulator includes ethylene glycol and disodium hydrogen phosphate, and the surfactant is polyethylene glycol; In the second surface treatment solution, the viscosity regulator includes ethylene glycol and disodium hydrogen phosphate, and the surfactant includes polyethylene glycol and polyoxyethylene laurate; In the third surface treatment solution, the viscosity regulator is ethylene glycol, and the surfactant includes polyethylene glycol and dodecylphenol polyoxyethylene ether; Preferably, the second surface treatment solution and the third surface treatment solution further include hexamethylenetetramine.

3. The method according to claim 2, characterized in that In the first surface treatment solution, the concentration of the nitric acid is 150-200 mL / L, the concentration ratio of the hydrofluoric acid to the nitric acid is 1:2-1:2.5, the concentration of the ethylene glycol is 100-150 mL / L, the concentration of the disodium hydrogen phosphate is 20-25 g / L, the concentration of the polyethylene glycol is 1-2 g / L, and the molecular weight is ≥6000; and / or, In the second surface treatment solution, the concentration of the nitric acid is 150-200 mL / L, the concentration ratio of the hydrofluoric acid to the nitric acid is 1:1.5-1:2, the concentration of the ethylene glycol is 80-100 mL / L, the concentration of the disodium hydrogen phosphate is 15-20 g / L, the concentration of the polyethylene glycol is 0.5-1 g / L, and the molecular weight is 1000≤≤2000, the concentration of the lauric acid polyoxyethylene ether is 0.2-0.4 g / L, and the concentration of the hexamethylenetetramine is 0.1-0.3 g / L; and / or, In the third surface treatment solution, the concentration of the nitric acid is 150-200 mL / L, the concentration ratio of the hydrofluoric acid to the nitric acid is 1:1-1:1.5, the concentration of the disodium hydrogen phosphate is 10-15 g / L, the concentration of the ethylene glycol is 20-50 mL / L, the concentration of the polyethylene glycol is 0.2-0.5 g / L, and the molecular weight is 200≤≤400, the concentration of the dodecylphenol polyoxyethylene ether is 0.1-0.2 g / L, and the concentration of the hexamethylenetetramine is 0.1-0.3 g / L.

4. The method according to claim 1, characterized in that: In the step S3 and the step S4, ultrasonic stirring is performed while the immersion treatment is performed, and the ultrasonic power is 800-2000W.

5. The method according to claim 4, characterized in that In step S2, when the surface roughness of the titanium alloy workpiece reaches a range of 15 to 18 μm, the thinning amount of the titanium alloy workpiece is controlled to be within 150 μm; and / or, In step S3, when the surface roughness of the titanium alloy workpiece reaches the range of 8 to 10 μm, the total thinning amount of the titanium alloy workpiece is controlled to be within 200 μm; and / or, In step S4, when the surface roughness of the titanium alloy workpiece reaches 5 μm or less, the total thinning amount of the titanium alloy workpiece is controlled to be within 300 μm.

6. The method according to claim 5, characterized in that In the three stages of the immersion treatment, if the total thinning amount of the titanium alloy workpiece reaches the maximum thinning amount requirement of the current stage, and the surface roughness still does not reach the target requirement of the current stage, the ultrasonic power of the ultrasonic stirring is adjusted, and / or the concentration of at least one of the passivator, the viscosity regulator and the surfactant in the surface treatment solution is adjusted.

7. The method according to claim 6, characterized in that The concentration of at least one of the passivating agent, the viscosity regulating agent and the surfactant is increased by 15-20%.

8. The method according to claim 7, characterized in that In step S2, if the surface roughness has not dropped below 18 μm when the thinning amount of the titanium alloy workpiece reaches 150 μm, the concentration of at least one of the nitric acid, ethylene glycol and polyethylene glycol in the first surface treatment solution is increased by 15-20% and the immersion treatment is performed again.

9. The method according to claim 7, characterized in that: In step S3, when the surface roughness of the titanium alloy workpiece reaches a range of 8 to 10 μm, the total thinning amount of the titanium alloy workpiece is controlled to be within 200 μm; If the surface roughness has not been reduced to less than 10 μm when the thinning amount of the titanium alloy workpiece reaches 200 μm, the ultrasonic power is reduced and the immersion is continued; If the surface roughness is still not reduced to below 10 μm when the ultrasonic power is reduced to 0, the concentration of at least one of the nitric acid, ethylene glycol, polyethylene glycol and lauric acid polyoxyethylene ether in the second surface treatment solution is increased by 15-20% and the immersion treatment is repeated.

10. The method according to claim 7, characterized in that In step S4, when the surface roughness of the titanium alloy workpiece reaches less than 5 μm, the total thinning amount of the titanium alloy workpiece is controlled to be within 300 μm; If the surface roughness has not been reduced to less than 5 μm when the thinning amount of the titanium alloy workpiece reaches 300 μm, the ultrasonic power is reduced and the immersion is continued; If the surface roughness is still not reduced to below 5 μm when the ultrasonic power is reduced to 0, the concentration of at least one of the nitric acid, ethylene glycol, polyethylene glycol and dodecylphenol polyoxyethylene ether in the third surface treatment solution is increased by 15-20% and the immersion treatment is repeated.

Citation Information

Patent Citations

  • Titanium alloy pretreatment method

    CN102787335A

  • Chemical abrasive flow polishing method for 3D printed titanium alloy

    CN109759942A

  • Method for determining components of chemical coarsening solution for passivating metal surface treatment

    CN116499955A

  • Chemical polishing method for complex surface of 3D printing titanium alloy part

    CN116590712A

  • Dip-coat binder solutions comprising metal dip-coat powder for use in additive manufacturing

    EP3995230A1